A 3-year follow-up of ceria-stabilized zirconia/alumina nanocomposite (Ce-TZP/A) frameworks for fixed dental prostheses. Issue 1 (January 2015) - Tanaka, Shinpei; Takaba, Masayuki; Ishiura, Yuichi; Kamimura, Emi; Baba, Kazuyoshi
Abstract Purpose Zirconia/alumina nanocomposite stabilized with cerium oxide (Ce-TZP/A) shows significantly higher mechanical strength than yttrium-oxide-partially-stabilized zirconia (Y-TZP) and allows post-sintered machining that does not require any subsequent treatment. The aim of this prospective study was to assess the clinical performance of veneered Ce-TZP/A frameworks for fixed dental prostheses. Methods Fifteen patients with 22 Ce-TZP/A fixed prostheses were included in this study. The fixed dental prostheses were cemented with resin cement (baseline) and were evaluated at baseline and at 1, 6, 12, 24 and 36 months after cementation. Clinical events, including fracture and loss of retention, secondary caries, and marginal integrity, were recorded. The biologic outcome was judged by comparing the pre-treatment and post-treatment bleeding on probing (BOP), and probing pocket depth (PPD) of the abutment teeth. Radiographic examination was also performed at 12, 24 and 36 months. Results The mean observation period was 35.9 ± 5.5 months. During this period, one abutment tooth was extracted due to root fracture and the survival rate was 95.2%. No significant change in BOP, PPD, and radiographic image was found during the 36-month follow-up period. Conclusion Within the limitations of this study, Ce-TZP/A was found to provide sufficient stability as a framework material in all regions. Special attention, however, must be paid to designing framework that provides sufficient support for the veneer. Furthermore, studies with longer observation periods and more patients are needed.